Antiracism And Feminism In Intersection: A Representation Study On Sue Monk Kidd’s The Invention Of Wings - Gaby Maryam Qordova Firdauzy (Fakultas Ilmu Budaya, 2025)
The study explores the intersection of antiracism and feminism in Sue Monk Kidd's novel The Invention of Wings. It focuses on how these ideas are represented through the experiences of the two main female characters. This study highlights the interconnected struggles of race and gender that lead women to be antiracist and feminist. Historically, women around the world have faced racial and gender discrimination. To fight this inequality, women unite as antiracists and feminists to challenge slavery and patriarchal society, ultimately striving for freedom and equality. This qualitative study employs Stuart Hall's theory of representation, especially the discursive approach, to analyze how language and narrative create the meanings of antiracism and feminism in the novel. Primary data from the text, including dialogues and narrations in the novel, are examined alongside secondary data to contextualize the findings within the author's socio-cultural background, the situation in the US during the 1800s, and its relevance to audiences in the 21st century. The study finds that the novel The Invention of Wings shows how antiracism and feminism intersect through its main female characters. Sarah, a white woman, faces limits because of her gender, while Handful, a Black slave, suffers from dehumanization and violence. Together, they create an interracial sisterhood that symbolizes their unity against racism and patriarchy. In conclusion, the novel portrays three aspects of antiracism and feminism, such as dehumanization, restrictions on career, and interracial sisterhood. This research also shows that the author emphasizes the ongoing problems of slavery's legacy and gender inequality, urging people to come together and take action against oppression while promoting justice in both past and present situations.
Reupload Repositori File 17 Maret 2026_Kholif Basri
Keywords: antirasisme; feminisme; diskriminasi ras dan gender